Interpersonal Relationship Needs of Employees of Private and Public Sector Organizations : A FIRO Perspective - Mitra, Debjani; Chatterjee, Ishita (Prabandhan: Indian Journal of Management, 2016)
The present study investigated the significant difference between various interpersonal relationship needs of the employees of private and public sector organizations ; 437 employees were selected from 55 public and private organizations in and around Kolkata, irrespective of the mode of operations. Fundamental interpersonal relationship orientation - Behavior (FIRO-B) scale developed by William Schutz in 1958 was administered to collect the data from the sample. For analysis of the data, descriptive statistics and one-way ANOVA were used. The findings revealed that significant difference existed between private and public sector employees in total wanted need; total behavior needs such as inclusion, control, as well as overall needs score. It was seen that private sector employees held stronger interpersonal needs than public sector employees. From the profiling of their FIRO-B score, it was seen categorically that employees from both the sectors fell in almost similar categories regarding individual need score as well as total and behavioral need scores. This research study would help management committees of these organizations to engage their employees in effective decision making as well as personality development training depending upon their interpersonal needs.